2022
DOI: 10.1158/0008-5472.can-20-0821
|View full text |Cite
|
Sign up to set email alerts
|

Loss of KMT5C Promotes EGFR Inhibitor Resistance in NSCLC via LINC01510-Mediated Upregulation of MET

Abstract: EGFR inhibitors (EGFRi) are standard-of-care treatments administered to patients with non–small cell lung cancer (NSCLC) that harbor EGFR alterations. However, development of resistance posttreatment remains a major challenge. Multiple mechanisms can promote survival of EGFRi-treated NSCLC cells, including secondary mutations in EGFR and activation of bypass tracks that circumvent the requirement for EGFR signaling. Nevertheless, the mechanisms involved in bypass signaling activation are understudied and requi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…KMT5C tri-methylates H4K20Me3 and acts as an epigenetic repressor ( 27 ). However, its role in breast cancer progression has not been addressed, and there are conflicting reports for other cancer types ( 2830 ). To test whether KMT5C regulates metastasis, we generated TNBC cells with stable over-expression of KMT5C and confirmed the increased tri-methylation at histone H4K20 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…KMT5C tri-methylates H4K20Me3 and acts as an epigenetic repressor ( 27 ). However, its role in breast cancer progression has not been addressed, and there are conflicting reports for other cancer types ( 2830 ). To test whether KMT5C regulates metastasis, we generated TNBC cells with stable over-expression of KMT5C and confirmed the increased tri-methylation at histone H4K20 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, deletion of lysine methyltransferase 5 C (KMT5C), an HMT responsible for histone H4 lysine 20 trimethylation (H4K20me3), upregulates lncRNA-LINC01510 and promotes MET transcription, leading to EGFR-TKI resistance in NSCLC through activation of the bypass pathway. 415 SET and MYND domain containing 2 (SMYD2) are highly expressed in ccRCC, and associated with multidrug resistance, including sunitinib in RCC. Mechanistically, SMYD2 binds to the promoter of miR-125b, inhibiting the expression of Dickkopf WNT signaling pathway inhibitor 3 (DKK3) and promoting proliferation and migration.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%
“…The hepatocyte growth factor (HGF) receptor, also known as MET, has been shown to be activated by miR-205/ERRFI1 and LINC01510. Thus, the PI3K/AKT pathway is enhanced, causing resistance to gefitinib, afatinib, erlotinib and osimertinib [ 49 , 50 ]. In a similar manner, ncRNAs such as miR-223, lncRNA GAS5 and hsa_circ_0005576 regulate IGF1R expression and subsequently influence the resistance of lung cancer cells to EGFR TKIs [ 32 , 51 , 52 , 53 ].…”
Section: Mechanisms Of Ncrnas Involved In Egfr Tki Resistancementioning
confidence: 99%
“…By directly targeting MET, miRNAs such as miR-1-3p and miR-206 attenuate gefitinib resistance by inactivating the Ras/Raf/MEK/ERK and PI3K/AKT/mTOR pathways [ 63 ]. In contrast, lncRNA LINC01510 promotes MET expression to maintain EGFR TKI resistance [ 50 ]. Moreover, emerging research has indicated that circBFAR functionally promotes the MET pathway by sponging miR-34b-5p [ 64 ], which can be hypothesized to cause EGFR TKI resistance.…”
Section: Mechanisms Of Ncrnas Involved In Egfr Tki Resistancementioning
confidence: 99%